Evaluation of Cardiovascular Risk in Hidradenitis Suppurativa Patients Using Heart Rate Variability (HRV) Analysis - Nevena Skroza; Alessandra Mambrin; Ilaria Proietti; Veronica Balduzzi; Nicoletta Bernardini; Anna Marchesiello; Simone Michelini; Ersilia Tolino; Salvatore Volpe; Patrizia Maddalena; Antonella Ciaramella; Gianfranco Raimondi; et al. (Cardiovascular Therapeutics)
Hidradenitis suppurativa (HS) is a chronic inflammatory skin disease associated with elevated prevalence of comorbidities, especially metabolic and cardiovascular diseases. We used a tool called Heart Rate Variability (HRV) in order to assess the correlation between HS and alterations of the sympathetic-vagal equilibrium in the autonomic cardiovascular regulation system. We found increased sympathetic activity, associated with a higher risk of cardiovascular disease. HS, according to our results, is an independent cardiovascular risk factor.